Commentaries, Catenae and Biblical Tradition Papers from the Ninth Birmingham Colloquium on the Textual Criticism of the New Testament : in association with the COMPAUL project - Houghton, H.A.G (Texts and studies, 2016)
In 2011, the European Research Council awarded Dr Hugh Houghton a Starting Grant to lead a five-year project investigating the earliest commentaries on Paul as sources for the biblical text.1 This project, known by its acronym COMPAUL, was intended to build on Dr Houghton's doctoral work analysing Augustine's gospel citations.2 The aim was to instigate a better understanding of commentaries and their contribution to the transmission of the New Testament in anticipation of two major editing projects: the Vetus Latina edition of the four principal letters of Paul and the Novum Testamentum Graecum Editio Critica Maior of all Pauline Epistles being planned by the IGNTP.